2002
DOI: 10.1002/polb.10092
|View full text |Cite
|
Sign up to set email alerts
|

Small‐angle neutron scattering investigation of structural changes in nafion membranes induced by swelling with various solvents

Abstract: The structure of Nafion-117 perfluorosulfonate ionomer membranes was investigated with small-angle neutron scattering techniques. Structural changes induced by the swelling of the membranes with water, alcohols, and dipolar, aprotic solvents were monitored at solvent-swelling levels ranging from approximately 2 vol % to greater than 50 vol %. Membranes swollen up to approximately 50 vol % solvent exhibited two scattering maxima, one known to be associated with ionic regions of the membrane structure and one kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 25 publications
8
72
1
3
Order By: Relevance
“…Previous studies have reported that the ionic peak shifts to lower q values (higher d spacing) as the volume fraction of solvent in the membrane increases due to expansion of the distance between the ionic domains. 52 Because the broad peak at q ≈ 0.04 Å -1 represents correlation between crystalline regions within the membrane, its position yields information about the nature of swelling within the ionic regions of Nafion separating the crystalline regions. Figure 9b shows the SANS profiles of the different hybrid systems prepared from Nafion.…”
Section: Nmr Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the ionic peak shifts to lower q values (higher d spacing) as the volume fraction of solvent in the membrane increases due to expansion of the distance between the ionic domains. 52 Because the broad peak at q ≈ 0.04 Å -1 represents correlation between crystalline regions within the membrane, its position yields information about the nature of swelling within the ionic regions of Nafion separating the crystalline regions. Figure 9b shows the SANS profiles of the different hybrid systems prepared from Nafion.…”
Section: Nmr Studymentioning
confidence: 99%
“…nique to identify structural organization within polymer systems and has been used extensively to study the nanostructure of Nafion membranes. [49][50][51][52] The random ionic clusters in Nafion act as a local cross-link and give rise to a local variation in cross-link density. Such network, on swelling in a low molecular weight solvent, exhibits competition between the osmotic pressure and the local elastic junction, resulting in local variation in polymer concentration.…”
Section: Nmr Studymentioning
confidence: 99%
“…3 The structure and alignment of PEM hydrophilic channels tends to be strongly influenced by membrane-electrode-assembly (MEA) preparation methods such as hot-pressing, 8,[11][12][13][14] polymer processing for membrane production, 5,6,[13][14][15] and swelling degree. [4][5][6][15][16][17] Thus, it is desirable to study the PEM in wet states in order to probe the proton conduction within and the hydrophilic channel structures of the functioning PEM. PEM hydrophilic channels have been primarily investigated by scattering techniques using neutrons and X-rays, [3][4][5][12][13][14][16][17][18] however, these techniques detect both systematic ordering of the hydrophobic polymer backbone and hydrophilic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][15][16][17] Thus, it is desirable to study the PEM in wet states in order to probe the proton conduction within and the hydrophilic channel structures of the functioning PEM. PEM hydrophilic channels have been primarily investigated by scattering techniques using neutrons and X-rays, [3][4][5][12][13][14][16][17][18] however, these techniques detect both systematic ordering of the hydrophobic polymer backbone and hydrophilic clusters. In contrast, various nuclear magnetic resonance (NMR) methods have been used to probe water dynamics in the hydrophilic clusters as well as the cluster structures.…”
Section: Introductionmentioning
confidence: 99%
“…O isopropanol, além de ser um bom solvente para as cadeias do Nafion, possui baixa constante dielétrica [111]. Ambos os fatores reduzem a intensidade do pico do ionômero 76 que pode auxiliar na determinação do espalhamento das partículas dispersas no polímero [37,159]. Adicionalmente, como mostrado na Tabela O pico do ionômero foi atribuído ao espalhamento devido à separação de fases hidrofóbicas e hidrofílicas no Nafion na escala nanométrica; a microestrutura do Nafion consiste de um conjunto de micelas invertidas cilíndricas fortemente unidas por interações eletrostáticas entre os pares iônicos.…”
Section: Compósito Nafion-sílicaunclassified